Advanced handover management framework for Mobile Router based on MCoA. (18th June 2012) - Yan, Zhiwei; Zhou, Huachun; Zhang, Hongke; Lo, Chi–Hsiang
In this paper, we design and implement a handover management framework which can integrate the multiple heterogeneous wireless networks (such as WLAN, GPRS and CDMA) with the support of Multiple Care–of–Address (MCoA) technology in the mobile network. The experimental results in a real network environment show that our proposed architecture can not only support the seamless handover, but also guarantee the scalability because of its modulised design. Besides, an adaptive handover trigger scheme and an access network selection scheme are proposed to initiate the handover and select the target access network intelligently.